ANALYSIS OF DENOTATION AND CONNOTATION MEANINGS IN THE SONG LYRIC “LA LA LOST YOU” BY NICOLE ZEFANYA (NIKI) - Hidayah, Annisa Ghaisani Dzatil; Bustam, Muhammad Rayhan (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
The purpose of this study is to examine the meaning of denotation and connotations in the lyrics of the song La La Lost You by NIKI solo singer from Indonesia who Go International. The formulation of the problem in this study is first. How is the denotation meaning of the lyrics of the song La La Lost You by NIKI? second What is the connotation of the lyrics of the song La La Lost You by NIKI? third What is the short meaning of the lyrics of the song La La Lost You by NIKI? and the method used in this research is to use a qualitative descriptive approach to reveal the meaning of denotation and connotation. The technique of data collection was done by using sentence expression analysis. While the data analysis technique is Roland Barthes Semiotics analysis. This study concludes that first, the connotative meaning contained in the lyrics of the song La La Lost You by NIKI is to tell about the bitter taste of being in a relationship with a lover who eventually has to break up, but he is often curious about how his ex is doing. Second, the denotative meaning contained in the song is telling about enjoying the beautiful sunset and thinking if he is on the subway and if I am driving will he take the L-train. Keywords: Connotation, Denotation, La La Lost You lyric, Meaning, Roland Barthes